Nature Inspired Fashion: The Design of Patterned Fabrics Inspired by the Ylang-Ylang (Cananga odorata) Flower with the Application of Fragrance Microencapsulation using Biomimicry - Innamia Indriani; Qyara Canthika Noor Ramadhania Henesh; Jauza Ratu Falysha; Ratu Puspa Indira Bhatari; Daniel Seroga Bara Pramesta; Hasya Az-Zahra; Ashari Budi Nugraha; Sabrina Ilma Sakina; Yan Yan Sunarya (Journal of Visual Art and Design, 2025)
Innovation in fragrance textiles reflects growing awareness of health, well-being, and aesthetic value. Nature has long served as a source of inspiration for designers and researchers, offering guidance for product innovation. Scents and fragrances are known to contribute positively to human well-being, and advances in textile technology have enabled the application of fragrance finishes through microencapsulation techniques. While visual appearance and fabric durability remain primary considerations for consumers, floral patterns—among the oldest and most favored textile design elements—continue to play an important role. This research employs mixed qualitative and quantitative methods to develop specialized textile products in the form of flower-patterned fabrics inspired by traditional Indonesian flora, specifically ylang-ylang (Cananga odorata). The study applies a biomimicry approach by using the ylang-ylang flower as both a visual and olfactory reference in textile design. Pattern development was combined with fragrance incorporation using a microencapsulation technique with PEG 6000 as the encapsulating agent. The resulting textile features a ylang-ylang floral pattern and releases a distinctive scent resembling the natural flower in bloom. This approach demonstrates the potential of integrating visual and sensory elements in textile design and supports future development of fragrance textile products to enhance consumer engagement.